1995
DOI: 10.3109/00365529509093233
|View full text |Cite
|
Sign up to set email alerts
|

Ulcerative Colitis and Indeterminate Colitis in the City of Malmö, Sweden a 25-Year Incidence Study

Abstract: This study has shown an increased incidence of ulcerative colitis and indeterminate colitis, and we have found no reason to believe that this is a spurious finding.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
27
0
3

Year Published

2004
2004
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(33 citation statements)
references
References 34 publications
3
27
0
3
Order By: Relevance
“…This idea is also supported by the increase in severe cases that could only be interpreted as real. Our incidence rates in UC (11.01) and CD (4.68) in the last five-year period (1997)(1998)(1999)(2000)(2001) were in the range as previously observed in high incidence Nordic countries [7,8,23,24] and they were much higher than the rates reported in Hungary two decades ago [12] . Most studies reported the peak onset of both UC and CD at late puberty -early adulthood period.…”
Section: Discussionmentioning
confidence: 48%
See 1 more Smart Citation
“…This idea is also supported by the increase in severe cases that could only be interpreted as real. Our incidence rates in UC (11.01) and CD (4.68) in the last five-year period (1997)(1998)(1999)(2000)(2001) were in the range as previously observed in high incidence Nordic countries [7,8,23,24] and they were much higher than the rates reported in Hungary two decades ago [12] . Most studies reported the peak onset of both UC and CD at late puberty -early adulthood period.…”
Section: Discussionmentioning
confidence: 48%
“…Previous studies in Europe suggested that the incidence was decreased from North to South [6,7] , but in the early nineties the European IBD Study Group found comparable rates in Southern and Northern Europe [8] . This tendency may be explained by the relative stable incidence in previous high incidence areas, whereas in previous low incidence areas the incidence rose continuously.…”
Section: Introductionmentioning
confidence: 99%
“…Population-based studies have demonstrated that in 4 % -10 % of adult patients with all IBD affecting the colon, it is impossible to distinguish between Crohn's disease and ulcerative colitis using current diagnostic techniques [87,88]. Establishing a definitive diagnosis has implications in terms of medical and surgical therapy, as well as clinical outcome.…”
Section: Introductionmentioning
confidence: 99%
“…Our data revealed a slight male predominance for UC and a mean age at diagnosis of 37.9 years, which is consistent with other Western and Asian studies. Population-based studies have found that the proportion of Western patients with proctitis ranges from 32% to 59%, while that among Asian patients is 25%-44% (1,(17)(18)(19)(20). In our study, the proportion of patients with proctitis was 32%.…”
Section: Discussionmentioning
confidence: 62%